Islamic Law and The Politics of Nation-State: Debating Citizenship Fiqh Through The Al-Maskut 'Anhu Discourse - Prihantoro, Hijrian Angga; Hasan, Noorhaidi; Masrukhin, Mohammad Yunus (Universitas Islam Negeri Jakarta, 2023)
The jurisprudential aspects of citizenship (known as fiqh al-muwāṭanah), emerging from the realm of ijtihād, have sparked considerable debate due to their theoretical nature. The term